Do external labour market incentives constrain bad news hoarding? The CEO's industry tournament and crash risk reduction - Chowdhury, Hasibul; Hodgson, Allan; Pathan, Shams (Journal of Corporate Finance, 2020)
We find that a CEO's industry tournament incentives (CITI) induce a CEO to undertake strategies that reduce the propensity of a firm to incur future stock price crash risk. CITI also has a mitigating effect on accounting techniques (such as, accrual manipulation, real earnings management, and financial restatement) used as channels for obfuscation and, therefore, is associated with a lower tendency to withhold bad news. CITI is more effective in reducing crash risk propensity when there is lower information quality and weaker external monitoring. Results are robust to firm governance controls, gender monitoring, and the specific personal attributes of CEOs. In short, CITI imposes on CEOs an incentive to brand themselves according to sustained visibility concepts.